اللغة العربية وأثرها على اللغات الاخرى (Journal of the College of Basic Education, 2026)
Since the late nineteenth century, the concept of "language"—its nature, function, and study—began to change. This shift prompted continuous efforts by Western scholars to study most of the world's languages descriptively, historically, and comparatively, aiming to develop a general theory or theories of "language" that reveal its true nature, origins, and evolution. They also sought to identify the general "laws" or principles common to human languages and to refine linguistic study methods and tools. This development led to the transfer of Arabic vocabulary into world languages through translation movements and cultural exchange. Islamic conquests, trade, and culture contributed to the spread of Arabic terms across the East and West. European languages borrowed many Arabic words related to sciences such as mathematics, astronomy, and medicine.Arabic also spread into Asian languages like Persian and Turkish, especially in religious terminology. In Africa, Arabic influenced local languages through religious and cultural contact.This linguistic blending reflects the civilizational role of the Arabic language throughout history.